Characterization of inflammatory infiltrate of ulcerative dermatitis in C57BL/6NCrl-Tg(HMGA1P6)1Pg mice. (October 2019) - De Biase, Davide; Esposito, Francesco; De Martino, Marco; Pirozzi, Claudio; Luciano, Antonio; Palma, Giuseppe; Raso, Giuseppina Mattace; Iovane, Valentina; Marzocco, Stefania; Fusco, Alfredo; Paciello, Orlando
Ulcerative dermatitis (UD) is an idiopathic, spontaneous and progressive disease typically affecting C57BL/6 aged mice with an unknown aetiopathogenesis. For this study, we evaluated 25 cases of UD in C57BL/6NCrl-Tg(HMGA1P6)1Pg mice. Formalin-fixed, paraffin-embedded skin samples were submitted to morphological investigations. Immunohistochemical analysis was performed to characterize and quantify inflammatory cells using CD3, CD45/B220, CD4, CD8 and IL-17 antibodies. Mast cell-bound IgE was investigated by immunofluorescence, whereas serum and cryopreserved skin samples were collected for molecular analysis. Student's t-test (two-tailed) was performed to assess significant differences between the two groups. Affected skin showed extensive areas of ulceration and diffuse, severe and mixed inflammatory infiltrates. No relevant changes were observed in control mice. Immunohistochemical analysis showed a predominant CD3 + CD4 + leukocyte population with fewer CD45/B220 and IL-17 immunolabelled cells and mast cell-bound IgE. Increases in TNFα, IL-1β and Il-6 mRNA expression were observed in the skin of affected animals compared to controls. Serum TNFα and IL-6 did not vary between affected and control mice. Inflammatory infiltrates and cytokine expression were consistent with both Th2/IgE and Th17 differentiation, a typical pattern of a type I hypersensitivity reaction. Overall, our data suggest an allergic-based aetiopathogenesis of UD in C57BL/6NCrl-Tg(HMGA1P6)1Pg mice.